2021
DOI: 10.6007/ijarbss/v11-i6/10058
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities for Newspapers in the Age of Digital Communication

Abstract: New media technology influences almost all aspects of traditional media, including subscriptions, readership, circulation, and advertising revenue. In particular, the possibility to access information and receive instant updates via the internet has threatened the existence of traditional newspapers. Therefore, this paper aims to review the challenges facing newspapers in the age of digital communication and how publishers can utilize digital technology to expand readership and maximize subscription and advert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Though much of the contemporary literature has investigated the role of social media (user-generated content) and its potential influence (Ashley & Tuten, 2015; Schivinski & Dabrowski, 2016) or fatigue (Bright et al, 2015), newspapers and magazines have historically been investigated for their coverage of many topics ranging from gender and ethnicity (Eagleman, 2015) to science and celebrity (Kamenova et al, 2014). Although the death of newspapers has often been declared (Hassan, 2021), for now, they still offer an excellent glimpse into societal consensus views and governmental foreign policies on a wide range of issues in any given country (e.g., climate change, Ford & King, 2015; ethnic representation, Bleich et al, 2016; mental health, Kenez et al, 2015). The same applies for television; whereas television tends toward sensationalism, the press still presents a more serious communication medium (Igartua & Muñiz, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Though much of the contemporary literature has investigated the role of social media (user-generated content) and its potential influence (Ashley & Tuten, 2015; Schivinski & Dabrowski, 2016) or fatigue (Bright et al, 2015), newspapers and magazines have historically been investigated for their coverage of many topics ranging from gender and ethnicity (Eagleman, 2015) to science and celebrity (Kamenova et al, 2014). Although the death of newspapers has often been declared (Hassan, 2021), for now, they still offer an excellent glimpse into societal consensus views and governmental foreign policies on a wide range of issues in any given country (e.g., climate change, Ford & King, 2015; ethnic representation, Bleich et al, 2016; mental health, Kenez et al, 2015). The same applies for television; whereas television tends toward sensationalism, the press still presents a more serious communication medium (Igartua & Muñiz, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even with the large population taken into account, India's poor internet penetration may prevent a substantial year-to-year fluctuation from signifying significant growth. Hassan et al (2021) similarly used semi-structured interviews to look at how the internet affects the UK's newspaper creation and distribution processes. The results demonstrated that newspapers began proactively engaging with customers to create various forms of relationship value while using the internet as an operational resource.…”
Section: Literature Review Theoretical and Conceptual Background Prin...mentioning
confidence: 99%